Analisis Wacana Digital Penggunaan Verbal Abuse dalam Konten Gameplay Stumble Guys Luthfi Halimawan - Muhammad Usamah Robbani; Heidy Arviani; Syafrida Febriyanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study discusses the discourse contained in Luthfi Halimawan's YouTube uploads in playing the game "Stumble Guys" which contains many words that are verbal abuse in speech. The use of sentences with elements of verbal abuse is quite concerning considering that the gameplay content of "Stumble Guys" is also watched by people of a minor age. In this study, researchers used a critical paradigm, with Rodney H. Jones's digital discourse analysis method. The findings from this digital discourse analysis explain that the "Stumble Guys" gameplay video content uploaded on Luthfi Halimawan's YouTube channel is a discourse on the use of sentences with elements of verbal abuse in gameplay content intended to make this content appear more liked by the audience. Luthfi produces content with elements of verbal abuse which he uses in titles, clips, highlights, and content in order to please his audience.